2010
DOI: 10.1186/1743-7075-7-72
|View full text |Cite
|
Sign up to set email alerts
|

Can bone loss be reversed by antithyroid drug therapy in premenopausal women with Graves' disease?

Abstract: ContextHyperthyroidism can lead to reduced bone mineral density (BMD) and increased fracture risk particularly in postmenopausal women, but the mechanism behind is still unclear.ObjectiveProspective examination of the influence of thyroid hormones and/or thyroid autoantibodies on BMD in premenopause.DesignWe have examined 32 premenopausal women with untreated active Graves' disease from time of diagnosis, during 18 months of antithyroid drug therapy (ATD) and additionally 18 months after discontinuing ATD. Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 43 publications
4
18
1
Order By: Relevance
“…Before treatment the GD patients who had osteoporosis in our study were characterized by being significantly older, being a greater number of years after menopause, having a significantly lower BMI, and having significantly higher serum total ALP, serum BAP, and serum NTX levels than the normal BMD group. Some studies have reported finding an inverse correlation between BMD and TRAb titers [8,16,18,19], but another study reported finding a positive correlation between BMD and TRAb titers [20]. The results of our study showed a negative correlation between TRAb titers and BMD in the DR, but the correlation coefficient was low.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Before treatment the GD patients who had osteoporosis in our study were characterized by being significantly older, being a greater number of years after menopause, having a significantly lower BMI, and having significantly higher serum total ALP, serum BAP, and serum NTX levels than the normal BMD group. Some studies have reported finding an inverse correlation between BMD and TRAb titers [8,16,18,19], but another study reported finding a positive correlation between BMD and TRAb titers [20]. The results of our study showed a negative correlation between TRAb titers and BMD in the DR, but the correlation coefficient was low.…”
Section: Discussioncontrasting
confidence: 52%
“…In our study, before the ATD treatment, the best predictor of BMD in the DR was BMD in the FN (β = 0.41, p < 0.0001). Patients' age, serum ALP and BAP values and BMI were also predictors of initial BMD in the DR. Several studies have tried to predict low BMD in GD patients on the basis of thyroid hormone levels, TSH receptor antibody titers, or bone marker levels but did not succeed [20,21]. A meta-analysis of studies on changes in BMD and fracture risk in hyperthyroidism showed a decreasing trend with age for spine BMD in untreated patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have reported TRAb to have an effect on bone independent of TSH and thyroid hormones (21,22). This raises the hypothesis that the aetiology of thyroid dysfunction may be of importance for bone health, but it needs confirmation in other studies.…”
Section: Discussionmentioning
confidence: 68%
“…However, the results of these and other studies are inconsistent (7,13,14,19,20). A few studies have investigated the importance of autoimmunity in thyroid disorders for fracture risk, but the results are inconclusive (21,22). Hence, the effect of thyroid function on fracture risk is not clear.…”
Section: Introductionmentioning
confidence: 70%
“…Although there are no available data on similar effects on the skeleton of agonist TSHR antibodies (TSHR-Abs) found in hyperthyroid Graves' disease, there is a distinct possibility that such antibodies may bind to and activate the skeletal TSHR. In support of this concept is a recent report that found an inverse relationship between bone density loss and TSHR-Ab levels (14).…”
mentioning
confidence: 78%